Realization problem for discrete-time positive linear systems - Kaczorek, Tadeusz (1932- ) (Zielona Góra: Uniwersytet Zielonogórski)
Sufficient conditions for the existence of a realization of a given proper transfer matrix are established. A procedure for calculation of a realization of a transfer matrix is given and illustrated by an example.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka